Comparison of Methods for Isolating Exosomes from Plasma Subjects with Normal and High Fat Percentages - Jacqueline Noboa-Velástegui; Juan Carlos León; Jorge Castro; Ana Fletes; Perla Madrigal; Iñaki Álvarez; Rosa Navarro (Life)
Adipose tissue is responsible for fat storage and is an important producer of extracellular vesicles (EVs). The biological content of exosomes, one kind of EV, provides information on aspects such as immunometabolic alterations. This study aimed to compare three plasma exosome isolation methods—using a commercial kit (CK), size exclusion chromatography (SEC), and differential centrifugation (DC)—and select the best one. Individuals categorized by normal and high body fat percentages were used. The DC and CK were proven to be the most advantageous out of the exosome isolation methods, so we suggest these methods for further protein and molecular analyses, respectively. Still, we emphasize the importance of selecting an appropriate methodology depending on the specific research objectives. At the same time, no statistical differences in exosome quality, morphology, total protein, or microRNA concentration were observed between individuals categorized by body fat percentage, so we suggest that the exosomal cargo varies in individuals with normal and high fat percentages.